Innovation and multi-level knowledge transfer using a multi-criteria decision making method for the planning of protected areas - José Manuel Guaita Martínez; Mónica de Castro-Pardo; Fernando Pérez-Rodríguez; José María Martín Martín (Journal of Innovation & Knowledge (JIK), 2019)
MCDM methods are useful to obtain information and generate knowledge useful for decision-making processes in multidisciplinary contexts. Particularly, when conflicts occur, knowledge is the key to start negotiation processes between stakeholders in order to achieve consensual solutions. The planning of protected areas is complex due to many competing uses of natural resources and the involvement of a large number of stakeholders. For the last ten years, participative MCDM methodologies have been carried out efficiently to reduce conflicts and allow to formalize stakeholder's participation in the policy development processes. In this paper, we propose a MCDM participative methodology in three levels that seeks to define management plans in protected areas. This method allows for the definition of management plans based on three levels of criteria that define the use of the natural area and provide a ranking of the main goals according to the stakeholders' priorities. The model was tested in two Spanish protected areas: Parque Natural de Lago de Sanabria y alrededores and Parque Natural de los Arribes del Duero. Firstly, the individual preferences of the most representative stakeholder groups were collected (Farmers, Business owners, Government and Scientists) and analyzed using two multi-criteria methods: AHP and GP. Moreover, a conflict index between stakeholders' groups was calculated. Results showed that conservation and development goals are the most preferred to consider for the planning of these areas. Furthermore, the most serious disagreement was found between farmers and scientists and between farmers and government about the wildlife conservation.
Keywords: Q20; C44; O39; O32; O38; Q28; 650; Protected areas; MCDM; AHP; Knowledge transfer; GP; Sustainable development